Optimal timber transportation planning in tropical hill forest using bees algorithm - Jamaluddin, Jamhuri (2022)
The selection of timber extraction techniques is the most important in timber harvesting operations. In Malaysia, crawler tractor is limited to extracting timbers on gentle slopes ≤ 20°, while log fisher can extract timber at a steeper slope ≤ 40°. The selection of timbers to be extracted on undulate topography is the primary concern in timber transportation planning (TTP), especially those related to selecting the extraction technique with the least cost. Combining these two techniques allows TTP to be linked to timber harvesting area models. The planning depends on the legal restrictions, fixed and variable costs, landing locations, as well as the existing and proposed road network. This study proposed a multi-objective linear programming model with Bees algorithm (BA) to find an optimal cost TTP for extraction, forest road, and landing locations. The model uses grid cell-sized 10 m x 10 m characterised with timber locations, volume and fixed and variable costs to represent the study area. Cells with timbers were assigned as -from node, and the model finds the following cells simultaneously on the extraction technique selection and forest road network. To limit the searching space from timbers to the first exit; landing, a geographically weighted regression (GWR) was used to select the candidate landings. The model finds the final destination from the landings attributed to the cumulative timber volume with the same steps. This model was tested and found the log fisher as a preferable extraction technique with 1,351 timbers than the crawler tractor with only 206 timbers. The extraction costs for the log fisher and the crawler tractor were RM 85,236.73 and RM 5,523.03, respectively. The costs to prepare the extraction trail were RM 1,315.00 for the log fisher and RM 4,930.00 for the crawler tractor. The hauling cost from 14 landings to the final destination was RM 817.95, and the cost for preparing the feeder road was RM 60,948.00. The preparation cost for the feeder road calculated from the model was 25.18% less than the feeder road proposed by Forestry Department of Peninsular Malaysia (FDPM) (RM 81,454.32). Given the finding of this study, the optimisation of the BA model has a better performance than the current practice of forest road planning in Malaysia. Although both practices have a similar objective to achieve sustainable timber harvesting with minimum impact on the environment and society, and low operational costs, the model developed in this study has shown better performance than the current practice. The sensitivity analysis conducted by changing the fixed and variable costs for crawler tractors, reducing the distance of log fisher trail and increasing the interval of landing locations shows the model capable of finding the least cost TTP solution. Overall, the model helps the forest engineer and the decision-makers to plan a suitable forest road networking for timber extraction and easily estimate the extraction costs, which the current practice is not able to.